Analisis Persepsi Dosen Terhadap Kebijakan Penggunaan Turnitin untuk Mendeteksi Plagiarisme Skripsi Mahasiswa - Zahra Aulia Rahmadianti; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Plagiarism is an academic violation that is quite serious so that the process of examining plagiarism is one of the prerequisites that must be carried out by academics in making a scientific paper including thesis. Advances in information technology make manual plagiarism checks increasingly difficult. Therefore, technological assistance that uses artificial intelligence is needed to be able to get comprehensive plagiarism analysis results. Turnitin is a software that uses artificial intelligence to detect plagiarism which is very popular and widely used by various institutions around the world. In the Faculty of Computer Science, Universitas Brawijaya, there is a policy that regulates the use of Turnitin to examine student thesis where supervisors play an important role in this policy. Therefore, a study was conducted to analyze lecturers' perceptions of the policy of using turnitin to detect student thesis plagiarism using qualitative methods. In the data collection process, semi-structured interviews were conducted involving 7 thesis supervisors as resource persons. The qualitative data that has been obtained from the interview process is then processed using the thematic analysis method with the help of NVivo software. From the analysis process, two main themes were found, namely the theme of the lecturer's perception of the use of Turnitin with 5 categories and 15 codes and the theme of the lecturer's perception of the policy of using Turntin with 3 categories and 15 codes.